Sistem Bilangan Bulat sebagai Dasar Teori Bilangan - Prihaten Maskhuliah; Aulia Salsabila Putri; Dewi Mawaddah Rumaf; Tita Mustikawati Selayar; Alfaris Syahdan Nurpratama; Iman Bugis; Erna Bugis (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
Integers are one of the fundamental concepts in number theory that serve as the foundation for studying various more complex mathematical topics. This article aims to describe the integer number system, including its definition, properties, and basic operations on integers. This article was written using a qualitative research method with a literature review approach, specifically through the examination of various books and scientific sources relevant to number theory. The results of the study indicate that the integer system consists of negative integers, zero, and positive integers, which possess the properties of closure, commutativity, associativity, distributivity, identity, and the inverse of addition. Furthermore, the operations of addition, subtraction, multiplication, and division of integers follow interrelated rules, thereby forming a consistent system for solving various mathematical problems. An understanding of the concepts, properties, and operations of integers is expected to serve as a strong foundation for studying number theory and to enhance a more comprehensive understanding of mathematical concepts.